THE CRUSTACEAN'S EXPORT-IMPORT MAPPING OF FISH QUARANTINE AND INSPECTION AGENCY (FQIA) JAKARTA I ON 2021-2022 PERIOD - Muhaemin, Moh; Yulanda, Meisi; Ruhenda, Uhen; Efendi, Eko (AQUASAINS, 2024)
Indonesia's crustacean has great potential fisheries business. The depletion of fisheries natural resources needs to be solved to avoid overfishing, especially for crustaceans. The study aim was to analyze crustacean diversity and mapping its products on export and import markets, as well as to analyze the sustainability of crustacean export-import across Indonesia. The study was conducted at FQIA Jakarta I on January until February 2023. The descriptive analysis method was used. The results of the study showed that Indonesia's fisheries export were higher than import activities. On crustacean exports, the highest destination country for lobster (Panulirus sp.) is Cina, the highest destination country for crab (Portunus pelagicus) is the USA, the highest destination country for mud crab (Scylla serrata) is Cina, and the highest destination countries for mantis shrimp (Squilla mantis) are Hongkong and Cina. Meanwhile, for imported crustaceans, snow crab (Chionoecetes opilio) came from Japan, and American lobster (Homarus americanus) came from Canada and USA. The overfishing has not occurred as illustrated for fishing grounds in Indonesia. It indicated by the average of annual catch value which has not higher than MSY catch. Keywords: Crustacea, fish market, fishing ground, annual catch, sustainable.